Academic segregation and the institutional success frame: unequal schooling and racial disparity in an integrated, affluent community. Issue 14 (26th October 2017) - Drake, Sean
ABSTRACT: In 1954, the US Supreme Court ruled that a system of 'separate but equal' schools for Blacks and Whites was 'inherently unequal', thus ending de jure segregation in American schools. Racial segregation, however, persists in American schools. While researchers have linked the continued segregation of schools to the racial and class segregation of neighbourhoods, school segregation also exists within neighbourhoods and independent of residential segregation. Drawing on two years of fieldwork at two dissimilar high schools, I unveil an unforgiving institutional culture and process of school segregation in an affluent, racially diverse Southern California suburb. A nationally ranked, elite comprehensive high school, where enrolment is predominantly Asian, White, and affluent, supports an exacting institutional success frame . Students who fall short of meeting this frame are subject to academic segregation ; they are jettisoned to a separate and unequal high school where the enrolment is disproportionately Black, Latino, and working-class. Korean American and Chinese American parents and students inspire the unyielding institutional success frame, and the frame results in academic segregation. Academic segregation reproduces ethnoracial and socioeconomic inequality in an integrated, affluent community, and the institutional success frame provides a rationale for institutional actors to legitimise and justify the inequality.